First Principles Study of Electronic, Vibrational, Elastic, and Thermodynamic Properties of Sc‐X (X = P, S, Se) Compounds - S. K. Yadav; S. Dahal; R. Khadka; B. Guragain; P. Pokharel; P. Oli; D. Adhikari (Engineering Reports)
ABSTRACT The available literature on Sc‐X (X = P, S, Se) compounds was comprehensively reviewed which revealed the unavailability of temperature‐dependent mechanical and thermodynamic properties of the materials to date. In this regard, the mixing properties of the compounds were investigated on the basis of density functional theory using Quantum ESSPRESSO codes. The obtained results of structural stability, electronic and mechanical properties of the work were found to be consistent with the available literature data which validates the present computational approach. The considered compounds were found to be stable and elastic constants satisfied the Born stability criteria. The phonon dispersion curves and phonon density of states were calculated which confirmed their dynamic stability. Using the same functionals, temperature‐dependent mechanical properties such as isothermal bulk modulus (BT), isoentropic bulk modulus (BS), BS‐BT, and the pressure derivative of the bulk modulus (dB/dP) were calculated in the temperature range 0–800 K. In thermodynamic properties, Helmholtz free energy, thermal energy, vibrational free energy, entropy, vibrational energy, thermal expansion, Grüneisen parameter, isochoric heat capacity (Cv), isobaric heat capacity (Cp), and Cp‐Cv, were also investigated in the temperature range.